Online Job Search Among Millennial Students in Malaysia - Fam, Soo-Fen; Soo, Jia Hui; Wahjono, Sentot Imam (JDM (Jurnal Dinamika Manajemen), 2017)
This study aims to determine the factors influenced online job search among millennial stu-dents in Malaysia Technical University Network (MTUN). A total of 300 university students through on-oneself-reported questionnaires were collected from four MTUN namely Uni-versiti Tun Hussein Onn Malaysia (UTHM), Universiti Malaysia Perlis (UniMAP), Univer-siti Teknikal Malaysia Melaka (UTeM) and Universiti Malaysia Pahang (UMP). This study performs descriptive analysis, reliability testing, correlation analysis and multiple regression analysis by using IBM-SPSS software version 22. The results indicate that factors such as user-perception, social networking sites, and smartphone technology are significantly related to the online job search enhancement. Amongst these three factors, user perception appears to be the strongest predictor toward online job search enhancement. This study concludes that besides consideration of the identified factors which lead to the successful adoption of online job search, effortless and interactive online job search websites in creating a convenient and favorable job search environment would be able to increase the use of online job search.